Modeling and Simulation in Clinical Pharmacology and Dose Finding. (27th February 2013) - Staab, A; Rook, E; Maliepaard, M; Aarons, L; Benson, C
Abstract : The breakout session 2 of the European Medicines Agency/European Federation of Pharmaceutical Industries and Associations Modeling and Simulation (M&S) workshop focused on two topics: when and how M&S should be used and would be accepted by the authorities for the dose‐regimen selection; and when and how M&S can be applied to register a dosing regimen without the need for a specific study. Each topic was introduced by an industry and regulatory perspective, followed by case examples for illustration (Table 1 ). CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e29; doi:10.1038/psp.2013.5 ; advance online publication 27 February 2013